Does Islamic social finance promote the quality of human resources? - Siswantoro Siswantoro; Ihsanul Ikhwan (Review of Islamic Social Finance and Entrepreneurship)
Purpose – This study aims to examine the contribution of Islamic Social Finance (ISF) distribution by sector (health, education, and economy) to the three dimensions of the Human Development Index (HDI) (health, education, and economy) and HDI aggregate in 34 provinces in Indonesia during the Covid-19 pandemic period (2020-2022). Methodology – A total of 102 panel data, a combination of data from 34 provinces in Indonesia (cross section) for a period of three years from to 2020-2022 (time series), were analyzed using a fixed effects panel model approach. Data were obtained from the National Board of Zakat (Badan Amil Zakat Nasional, BAZNAS) and the Central Statistics Agency (Badan Pusat Statistik, BPS). Findings – The main research results show that ISF channeled for human development purposes (in total) significantly increases the aggregate HDI by 0.008538%. However, the ISF distributed by sector (health, education, and economy) has a positive but insignificant impact on the three dimensions of HDI (health, education, and economy). This makes sense because the proportion of ISF distribution for these three fields tends to be small compared with other sectors. Implications – It is recommended that ISF fund allocation be more efficient, equitable, fair, and capable of reaching all aspects of human life. In addition, efforts must be made to collect ISF funds more effectively through technological integration. Originality – Most previous research has only tested Islamic social finance against HDI in aggregate, not by dimension, so the results were less specific.